Prognostic significance of serum apelin-13 and galectin-3 concentrations as potential indicators of severity and mortality in pediatric acute respiratory distress syndrome - Taşar, Serçin; Alacakır, Nuri; Bulut, İsmail and Tapcı, Ayşe Esra and Kırtıl, Gül and Koçoğlu, Naz and Saç, Rukiye Ünsal and Taşar, Medine Ayşin (The Turkish Journal of Pediatrics, 2026)
Background. The predictive and prognostic significance of apelin and galectin-3 as biomarkers in pediatric acute respiratory distress syndrome (PARDS) and lung injury has remained limited. This study examined the association between serum apelin-13 and galectin-3 levels, PARDS severity, and patient outcomes. Methods. The study included children aged 1 month to 18 years diagnosed with PARDS on admission to a pediatric intensive care unit, alongside age- and sex-matched outpatient controls. PARDS was diagnosed and classified by severity according to Second Pediatric Acute Lung Injury Consensus Conference (PALICC-2) guidelines, based on oxygenation indices for non-invasive and invasive ventilation. Exclusion criteria included prior transplants, chronic lung disease, cyanotic congenital heart disease, prolonged ventilation, and other major conditions. After informed parental consent, 3 mL of peripheral venous blood was collected from all participants. Serum samples for apelin-13 and galectin-3 were stored at −80°C and analyzed using commercial enzyme-linked immunosorbent assay (ELISA) kits. Demographic, clinical, and laboratory data were systematically recorded for analysis. Results. The study and control groups were comparable in age and gender. Patients had significantly lower hemoglobin, hematocrit, red blood cell, calcium, and phosphorus levels, and higher neutrophil counts, C-reactive protein, and liver enzymes. Apelin-13 levels did not differ significantly between groups, wheras median galectin-3 levels were significantly higher in patients (p=0.003). Apelin-13 levels were significantly lower and galectin-3 levels significantly higher with increasing PARDS severity. Severe PARDS was associated with lower PaO2/FiO2 ratios, arterial pH, and higher ventilator pressures. Mortality was 36.4% in severe and 22.7% in moderate PARDS. Serum galectin-3 level was the sole independent predictor of mortality (OR: 1.20, 95% CI 1.02–1.39, p=0.02). Conclusion. Although the apelin/APJ system’s role in acute lung injury is known, its diagnostic and prognostic value in PARDS requires further study. Galectin-3 levels correlate with disease severity and outcomes, highlighting the need for larger, age- and phenotype-homogenized studies to confirm its role as an independent mortality predictor.